Нормативно-правове забезпечення соціального захисту особового складу державної служби спеціального зв’язку та захисту інформації України - Вапнярчук, Н. М. (НДІ ПЗІР НАПрН України, 2022)
У статті проаналізовано чинне законодавство щодо соціального забезпечення особового складу Державної служби спеціального зв’язку та захисту інформації України. Зазначено, що з урахуванням того, що в Україні на сьогодні триває війна з російською федерацією особливого значення набуває переосмислення специфіки соціального захисту особового складу Державної служби спеціального зв’язку та захисту інформації України, котрі є людьми, виконуючими особливу роботу, прямо чи опосередковано спрямовану на захист Вітчизни. Актуальність питання забезпечення соціального захисту констатована також у рішеннях Ради національної безпеки і оборони України «Про Концепцію реформування Державної служби спеціального зв’язку та захисту інформації України» та «Про Стратегію воєнної безпеки України». Проаналізувавши чинне законодавство щодо соціального забезпечення особового складу Державної служби спеціального зв’язку та захисту інформації України зроблено висновок, що не дивлячись на великий обсяг нормативно-правових актів у цій сфері, це не завжди свідчить про забезпечення цілісного та комплексного соціального захисту даної категорії осіб. Оскільки немає єдиного підходу, так як положення про окремі види соціальних гарантій, пільг, послуг, переваг, виплат для особового складу Державної служби спеціального зв’язку та захисту інформації України формуються хаотично, за різними підходами до їх сутності і призначення, фінансування та порядку реалізації. І як наслідок, хоча соціальне забезпечення досліджуваної категорії осіб передбачено низкою нормативно-правових актів, багато питань залишається не вирішених особливо в умовах сьогодення. Тому бракує єдиного законодавчого акту, відповідно до якого було б визначено консолідовані та взаємоузгоджені стандарти та принципи побудов усієї структури соціального забезпечення у досліджуваній сфері. Problem setting. The article analyzes the current legislation on social security for the personnel of the State Service for Special Communications and Information Protection of Ukraine. It is noted that, taking into account the fact that the war with the Russian Federation is currently ongoing in Ukraine, the rethinking of the specifics of social protection for the personnel of the State Service for Special Communications and Information Protection of Ukraine, who are people performing special work directly or indirectly aimed at National defense. The relevance of the issue of ensuring social protection is also stated in the decisions of the National Security and Defense Council of Ukraine “On the Concept of Reforming the State Service of Special Communications and Information Protection of Ukraine” and “On the Military Security Strategy of Ukraine”. Analysis of recent researches and publications. Issues of social protection were studied by such domestic scientists as V. M. Andriyev, N. B. Bolotina, M. I. Inshin, M. I. Derevyanko, M. M. Klemparskyi, O. L. Kuchma, K. Yu., L. I. Shumna, V. I. Shcherbyna, M. M. Shumylo, O. M. Yaroshenko, and others. At the same time, insufficient attention is paid to the social protection of the personnel of the State Service of Special Communication and Information Protection of Ukraine. Target of research is to analyze the current legislation on social security for the personnel of the State Service for Special Communication and Information Protection of Ukraine. Article’s main body. Today, in the domestic legal system, the social security of the personnel of the State Service for Special Communications and Information Protection of Ukraine is regulated by a number of normative legal acts of various powers. Characterizing in general the given multiplicity of acts, it should be noted that we are not talking about a system of legislation with mutually agreed connections between its elements, a single conceptual and categorical apparatus, principles, procedures, standards. The legislation regulating the social security of the personnel of the State Service for Special Communications and Information Protection of Ukraine is extremely fragmented, cluttered with a large number of different regulatory and legal acts. Conclusions and prospects for the development. Having analyzed the current legislation on the social security of the personnel of the State Service of Special Communications and Information Protection of Ukraine, it was concluded that, despite the large volume of normative legal acts in this area, this does not always indicate the provision of integral and comprehensive social protection of this category of persons. Since there is no single approach, as the provisions on certain types of social guarantees, benefits, services, advantages, and payments for the personnel of the State Service for Special Communication and Information Protection of Ukraine are formed chaotically, according to different approaches to their essence and purpose, financing and implementation procedure. And as a result, although the social security of the studied category of persons is provided for by a number of normative legal acts, many issues remain unresolved, especially in today’s conditions. Therefore, there is a lack of a single legislative act, according to which consolidated and mutually agreed standards and principles of construction of the entire social security structure in the researched area would be determined.
Keywords: соціальний захист; матеріальне забезпечення; соціальні гарантії; національне законодавство; державна служба спеціального зв’язку та захисту інформації України; державні службовці; військовослужбовці; працівники; social protection; material support; social guarantees; national legislation; State Service for Special Communications and Information Protection of Ukraine; civil servants; military personnel; employees